A combined model for river health evaluation based upon the physical, chemical, and biological elements. (January 2018) - Zhang, Xiang; Meng, Yu; Xia, Jun; Wu, Bi; She, Dunxian
Highlights: Proposed RES index referred to the ratio of environmental flow to streamflow. Combined RES with the Tennant method for aquatic habitat evaluation. Evaluation index system of river health considering physical, chemical and biological elements was structured. Proposed fuzzy matter-element & projection-pursuit combined model for comprehensive evaluation. Results provide knowledge to improve of river health and water allocation. Abstract: Rivers provide many services to humans, however, globally, they have been historically impacted from over-exploitation for human needs. Such impacts are likely to increase into the future leading to poorer river health and the service functions provided by rivers are being lost. This study focused on the river health evaluation for river protection and sustainable water management. Eight indices were selected to structure an evaluation index system, consisting of physical, chemical, and biological elements, for river health evaluation. Among them, a new index, Ratio of Environmental flow to Streamflow (RES), was proposed to evaluate the satisfaction degree of environmental flow and to establish a common standard for the comparison of habitat quality among different rivers. A combined model consisted of fuzzy matter-element and projection pursuit models was established for the evaluation of river health, which was adopted to convert several indices in the evaluation index system to a comprehensive indicator. The Huai River Basin was selected as the case study area. The results showed that the river health of the whole Huai River was at the medium level. Four river reaches such as Reach I, II, IV and V were in the middle level, while only Reach III was at the sub-healthy level. This study is expected to provide scientific knowledge for the improvement of river health and water allocation.